Analisis Sektor Ekonomi Basis Dan Non Basis di Kabupaten Ende Periode 2013-2017 - Estherlina Sagajoka (ANALISIS, 2019)
This research aims to determine the economic sector of base and Non-base in Ende district in the period 2013-2017. The methods used in this study are quantitative descriptive. The analysis tool used is the Location Quotient (LQ) Analysis of the Location Quotient analysis results showed that the base sector of the 2013-2017 period is 1). Large and retail sectors, car repair and motorcycles (1.42); 2). Transportation and warehousing sectors (1.28); 3). The Real Estate sector (1.17); 4) Industrial processing sector (1.14); 5). Education services sector (1.13); 6). Other services Sectors (1.12); 7). Water procurement sector waste treatment Limbag and recycling (1.10); 8). Construction sector (1.02). And non-base sectors are 1). Corporate services sector (0.03); 2). The accommodation provision sector drinking food (0.49); 3). Information and communication sectors (0.60); 4). Health services and social activities sectors (0.82); 5). Sector of government administration, defence and Social Security mandatory (0.84); 6). Agriculture, Forestry and fisheries sector (0.92); 7). Supply and Gas procurement sector (0.93); 8). Financial services and insurance sector (0.98); and 9). Mining and excavation sector (0.99). The base sectors can be the leading sector for the economic development of Ende District also can be a trigger for other economic sectors that will impact the increase in revenues, increase in PDRB and economic growth in Ende District in general.